2018
DOI: 10.1002/jcp.27761
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anticancer action of quercetin and curcumin against triple‐negative breast cancer cell lines

Abstract: Women with the breast cancer type 1 susceptibility protein (BRCA1) mutation and loss of BRCA1 expression are reported to have an increased risk of triple‐negative breast cancer (TNBC). Targeting BRCA1 modulation might offer a therapeutic option to treat TNBC patients. Our studies detected that BRCA1 is poorly expressed in TNBC cell lines and highly expressed in ER+ breast cancer cell lines. To modulate BRCA1 expression, we tested two different dietary components to find out if any would induce tumor suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 67 publications
(142 reference statements)
7
60
0
Order By: Relevance
“…Meanwhile, a correlation between β-catenin and HAT has been reported in other cancers [100]. Recently, we showed that quercetin enhances epigenetically silenced BRCA1 expression in TNBC [102]. Furthermore, our study revealed that the combined effect of quercetin and curcumin enhanced BRCA1 expression synergistically and the BRCA1 promoter histone H3K9 acetylation was significantly increased with the combined treatment in a TNBC cell line (MDA-MB-231) [10].…”
Section: Quercetin Modulates Brca1 Expression Levelsupporting
confidence: 57%
“…Meanwhile, a correlation between β-catenin and HAT has been reported in other cancers [100]. Recently, we showed that quercetin enhances epigenetically silenced BRCA1 expression in TNBC [102]. Furthermore, our study revealed that the combined effect of quercetin and curcumin enhanced BRCA1 expression synergistically and the BRCA1 promoter histone H3K9 acetylation was significantly increased with the combined treatment in a TNBC cell line (MDA-MB-231) [10].…”
Section: Quercetin Modulates Brca1 Expression Levelsupporting
confidence: 57%
“…It has been reported that quercetin blocks the progression of diverse human tumors, such as oral cancer, breast cancer, and NSCLC . In this work, the function of quercetin in reversing the radioresistance of NSCLC cells was studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that quercetin blocks the progression of diverse human tumors, such as oral cancer, breast cancer, and NSCLC. 14,27,28 In this work, the function of quercetin in reversing the radioresistance of NSCLC cells was studied. It was demonstrated for the first time that quercetin exerts an anti-cancer effect in vitro via modulating miR-16-5p and WEE1 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, T1 inhibited cancer growth in several BC cell lines (MCF-7, MDA-MB-231, SKBR3, MDA-MB-453) in vitro, at least partially by affecting the function of this gene [122]. Triple-negative breast cancer (TNBC), which represents an aggressive BC subtype with poor prognosis, is highly associated with mutations of tumorsupressor BRCA1 [125][126][127]. However, quercetin and curcumin (CUR) dose-dependently inhibited cell survival and migration of TNBC cell lines in vitro via modulation of BRCA1 expression.…”
Section: Impact Of Phytochemicals On Histone Chemical Modifications Imentioning
confidence: 99%
“…However, quercetin and curcumin (CUR) dose-dependently inhibited cell survival and migration of TNBC cell lines in vitro via modulation of BRCA1 expression. The authors of the study concluded that these synergistically acting natural compounds repressed the silencing of BRCA1 via an increase in H3 lysine acetylation of its promoter [127]. Moreover, anticancer efficacy of crystal lapiferin derived from the traditional Algerian plant, Ferulaves ceritensis, was evaluated in human BC cells.…”
Section: Impact Of Phytochemicals On Histone Chemical Modifications Imentioning
confidence: 99%